PENGARUH EDUKASI KESEHATAN TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE II RAWAT JALAN DI RUMAH SAKIT ISLAM SULTAN HADLIRIN JEPARA - Hudiyanto Hudiyanto; Akbar Amin Abdullah; Feri Catur Yuliani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Based on medical record data in 2024 at Sultan Hadlirin Islamic Hospital Jepara, of 120 outpatients with Type 2 Diabetes Mellitus, only 65 people (54.1%) were recorded as compliant in following the control and treatment schedule regularly. Initial interviews with 10 patients showed that 8 people (80%) had never received systematic health education regarding the treatment they were undergoing. Lack of compliance in taking medication can have an impact on increasing the risk of complications and reducing the quality of life of patients. The aim was to determine the effect of health education on medication compliance in Type 2 Diabetes Mellitus patients. Methods: The research design used a pre-experimental with a one group pretest-posttest approach. The study was conducted at the Outpatient Polyclinic of Sultan Hadlirin Islamic Hospital Jepara in June–July 2025. The number of samples was set at 55 respondents. The results of data analysis using the Spearman test showed a value of r = 0.512 with p = 0.000 (p <0.05). The conclusion of this study proves that health education has a significant effect in increasing medication adherence in Type 2 Diabetes Mellitus patients.